2015
DOI: 10.1128/aac.04376-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacies of Tedizolid Phosphate, Vancomycin, and Daptomycin in a Rabbit Model of Methicillin-Resistant Staphylococcus aureus Endocarditis

Abstract: Staphylococcus aureus is a common cause of skin and soft tissue infections and invasive disease, such as bacteremia and endocarditis. Tedizolid, the microbiologically active moiety of the prodrug tedizolid phosphate (TZD), is a novel oxazolidinone approved for treatment of acute bacterial skin and skin structure infections caused by Gram-positive bacteria, including strains of methicillin-resistant S. aureus (MRSA). Tedizolid phosphate is rapidly cleaved in the bloodstream to yield the active component, tedizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
2
15
1
Order By: Relevance
“…Accordingly, antitoxin antibodies plus protein synthesis inhibitors, like linezolid and tedizolid phosphate, are expected to work together to further enhance survival outcomes by neutralizing preformed toxins and preventing their cytotoxic effects in the lungs, as well as inhibiting the bacterial production of these toxins. The superior protective efficacy of tedizolid phosphate over that of vancomycin in the rabbit MRSA USA300 pneumonia model stands in contrast to the superior protective efficacy of vancomycin over that of tedizolid phosphate in the rabbit model of aortic valve endocarditis (20). One potential explanation for this discrepancy could be that the USA300/SF8300 clinical strain used in the rabbit pneumonia model is known to naturally hyperproduce alpha-toxin and PVL (21), which together play critical roles in the pathogenesis of necrotizing pneumonia (5,7).…”
Section: Discussioncontrasting
confidence: 41%
“…Accordingly, antitoxin antibodies plus protein synthesis inhibitors, like linezolid and tedizolid phosphate, are expected to work together to further enhance survival outcomes by neutralizing preformed toxins and preventing their cytotoxic effects in the lungs, as well as inhibiting the bacterial production of these toxins. The superior protective efficacy of tedizolid phosphate over that of vancomycin in the rabbit MRSA USA300 pneumonia model stands in contrast to the superior protective efficacy of vancomycin over that of tedizolid phosphate in the rabbit model of aortic valve endocarditis (20). One potential explanation for this discrepancy could be that the USA300/SF8300 clinical strain used in the rabbit pneumonia model is known to naturally hyperproduce alpha-toxin and PVL (21), which together play critical roles in the pathogenesis of necrotizing pneumonia (5,7).…”
Section: Discussioncontrasting
confidence: 41%
“…We demonstrated that the combination of tedizolid plus rifampin or vancomycin plus rifampin was more active than no treatment in this model, in which the infected foreign body was retained. Although the activity of tedizolid against methicillin-resistant S. aureus (MRSA) has been analyzed in several experimental studies, such as in a model of experimental endocarditis in rabbits (17) and a model of catheter-related biofilm infection in mice (18), the role of tedizolid against MRSE in experimental osteomyelitis has not been well studied. Successful animal models of osteomyelitis and foreign body infection have been established in rabbits, dogs, chicks, guinea pigs, and rats (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In nonclinical studies, tedizolid phosphate demonstrated promising efficacy results across a range of animal infection models (Chan et al, 2009;Louie et al, 2011;Lepak et al, 2012); phase 3 trials showed that administration of intravenous or oral tedizolid phosphate (200 mg once daily) for 6 days achieved noninferior efficacy in acute bacterial skin and skin structure infections compared with 10 days of linezolid therapy (Prokocimer et al, 2011Fang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%